Asymptotic Behavior of Iterates of a Generic Cyclical Nonexpansive Mapping. (2nd January 2022) - Zaslavski, Alexander J.
Abstract: In this paper we consider a complete metric space of cyclical nonexpansive mappings acting on a union of two sets in a complete hyperbolic space with an empty intersection. Using Baire category approach, we show for most mappings the distance between iterates converges to the distance between these two sets.